Patient Endorsement of the Outcome Measures in Rheumatology (OMERACT) Total Joint Replacement (TJR) clinical trial draft core domain set - Singh, Jasvinder A. (BMC Musculoskelet Disord, 2017)
BACKGROUND: A patient- and surgeon-Delphi-derived Outcome Measures in Rheumatology (OMERACT) draft core domain set for total joint arthroplasty (TJR) trials was recently developed. Our objective was to obtain further patient stakeholder endorsement of draft core domain set for TJR clinical trials. METHODS: We surveyed two patient groups: (1) OMERACT patient partners; and (2) patients who had undergone hip or knee TJR. Patients received an introductory email with explanations about the core domain set and instructions to rate the core domains, i.e., important aspects, of OMERACT TJR clinical trial draft core domain set. Rating was on a nominal scale, where 1–3 indicated a domain of limited importance, 4–6 an important, but not critical domain, and 7–9 a critical domain. We used Mann–Whitney test (a non-parametric test) to compare the distribution of ratings between the two groups. RESULTS: Thirty one survey participants from the OMERACT patient partner group and 118 knee/hip TJR patients responded with response rates of 66 and 80%, respectively. Majority of the survey respondents were female, 87 vs. 53%, and were 55 years or older, 57 vs. 94%. Median (interquartile range [IQR]) scores for six core domains by OMERACT and knee/hip TJR patient groups were, respectively: pain, 8 [8, 9] and 9 [8, 9]; function, 9 [8, 9] and 9 [8, 9]; patient satisfaction, 8 [8, 9] and 8 [7, 9]; revision surgery, 7 [7, 8] and 7 [5, 9]; adverse events, 8 [7, 9] and 8 [6, 9]; and death, 9 [6, 9] and 9 [4, 9]. No statistically significant differences in rating were noted for any of the six core domains between the two groups (p ≥ 0.31). Among the additional domains, ratings for patient participation did not differ by group (p = 0.98), but ratings for cost were significantly different (p = 0.005). Patients provided qualitative feedback regarding core domains, and did not propose any modifications to the draft core domain set. CONCLUSIONS: Two separate patient stakeholder groups endorsed the OMERACT TJR draft core domain set for TJR trials. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12891-017-1464-x) contains supplementary material, which is available to authorized users.